MADRASAH IBTIDAIYAH (MI) TEACHERS CREATIVITY DEVELOPMENT MAPPING AND STRATEGIES IN LEARNING IN THE ERA OF THE COVID 19 PANDEMIC IN WEST JAVA - Rosyidi, Unifah (International Journal of Business, Law, and Education, 2022)
Private school Madrasah Ibtidaiyah (MI) teachers in Klari District, Karawang Regency-West Java are still very limited in their opportunities to participate in various trainings, meanwhile the creativity of teachers in teaching is currently a very important thing to pay attention to. Loss learning in learning can occur, one of which is when teachers do not have the ability and creativity in overcoming all the limitations that arise in distance learning that are set due to the covid 19 pandemic. The phenomenon of loss learning is vulnerable to overshadowing in the online learning system. This study explains that the training model based on material presentation and discussion as well as questions and answers for four years through a periodical theme format has shown teacher satisfaction as training participants with the delivery of the material provided by 76.2%. These results indicate that the training materials can be understood by most of the Madrasah Ibtidaiyah teachers, and it is necessary to follow up the evaluation of how the impact of the training in increasing the creativity of Madrasah Ibtidaiyah teachers is in the pandemic era.